Editorial - Isilda Teixeira Rodrigues, Maria Helena Roxo Beltran , Deividi Marcio Marques, Fabiana Dias Klautau (História da Ciência e Ensino: construindo interfaces, 2022)
Editorial do volume 25 especial da Revista História da Ciência e Ensino: construindo interfaces.